Development of National Procedural Law in the Second Half of the XIX – Early XX Centuries - D. V. Slynko; L. I. Kalenichenko (Law and Safety)
The authors have studied one of the current historical and legal problems concerning the development of procedural law in the Ukrainian lands, which were part of the Russian and Austro-Hungarian Empires in the second half of the XIX – early XX centuries. Based on the analysis of scientific literature and relevant regulatory material, it has been noted that the beginning of the reform of procedural legislation of the Russian Empire can be considered the introduction of the institution of forensic investigators by the imperial decree in June 1860. Thus, the preliminary investigation was separated from the police, and investigators were part of the staff of the judicial department. The next stage was the judicial reform of 1864. As a result of the reform, the judicial system and procedural law were completely changed. Substantive law was also partially amended under that influence; there was the separation of criminal proceedings from the civil one; procedural norms of administrative justice began to be formed in the Ukrainian lands during that period, and a new branch of knowledge within legal science emerged, which was aimed at searching for the essence and nature of procedural law. The development of procedural law in the Ukrainian lands, which were part of the Austrian and, since 1868, the Austro-Hungarian Empires, was characterized by the obsolescence and imperfection of procedural legislation and its focus on the establishment of imperial positions. At the same time, it is possible to state its certain democracy and succession. It has been concluded that national procedural law during that period was characterized by the preservation and strengthening of certain features of the medieval process (secular nature, rationality, phasing), by the separation of procedural law from the substantive, by the formation of procedural branches of law, by the codification of procedural legislation, by the separation of administrative proceedings from criminal and civil proceedings; the functions and competence of the authorities and their officials were differentiated.